Fast fabrication of Co3O4 and CuO/BiVO4 composite photocatalysts with high crystallinity and enhanced photocatalytic activity via ultrasound irradiation - Yu, C.; Yang, K.; Yu, J.; Cao, F.; Li, Xin Yong; Zhou, X. (2011)
A facile and efficient approach for the fabrication of Co3O4 and CuO/BiVO4 composite photocatalysts was developed by intense ultrasound irradiation at room temperature. The as-synthesized samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), photoluminescence (PL) spectroscopy, UV–vis diffuse reflectance spectra (UV–vis DRS), and Brunauer–Emmett–Teller (BET) surface areas. The photocatalytic activity of the composite catalysts was evaluated by photocatalytic degradation of acid orange II under visible light (λ > 420 nm) irradiation. Results showed that under intense ultrasonic irradiation, the precursors of copper acetate and cobaltous acetate could transform into CuO and Co3O4, respectively and the amorphous BiVO4 can easily crystallize to highly crystalline BiVO4. The composite photocatalysts exhibited much higher photocatalytic activity than that of pure BiVO4. The enhanced photocatalytic performance could be attributed to the high crystallinity of BiVO4 and the formed p–n heterojunction of Co3O4/BiVO4 or CuO/BiVO4. These two factors can effectively suppress the recombination of photogenerated hole–electron pairs.